(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
A “digital footprint” and a “digital shadow” are essentially the same concept, referring to the trail of data a person leaves behind when using the internet, including the websites visited, emails sent, and information submitted online, essentially creating a traceable online presence; "digital shadow" is simply a more figurative way of describing this data trail.